(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Illegal Drugs have been part of our society for a long period of time, But suddenly, it is illegally abused by those people who only have interests for their own sake, and to fulfill their satisfaction as a result of using illegal drugs affects their mind and their way of thinking so they result from committing crimes. Using illegal drugs has many negative effects on our bodies. Substance abuse and mental health are linked because the psychological effects of drug addiction cause changes in your body and brain. From an outside perspective, someone with drug addiction looks like they are repeatedly making bad choices and ignoring reasons that may result in drug-related crimes as they are not aware of what they are doing and what maybe the effect of their bad decisions caused by taking or dealing drugs. Using Illegal drugs shows some negative effects that can affect not only the people using it. It can also affect the people in his/ her surroundings. The results of the study about the implications of using illegal drugs in the increase of criminality at Bagong Silang, Caloocan City, indicate that while an individual is under the influence of drugs, there is a high chance that that individual might commit a crime because drugs affect his/her way of thinking and altered the reasoning of an individual. The researcher suggests some preventive measures on how the police and barangay might lessen the criminality because of using illegal drugs. The study also revealed that the respondents “Strongly Agree” that Drugs are one of the implications of the increase in criminality in Bagong Silang, Caloocan City. The study also recommended that groups of people or organizations help individuals who are using illegal drugs to cope with their problems and provide a better solution. The researchers recommend conducting seminars and programs about the negative effects of illegal drugs on an individual and how can the use of illegal drugs lead to an increase in criminality, and also to strengthen the security in the community to prevent the commission of crime because of using illegal drugs.